A case of PD-L1 negative advanced pulmonary sarcomatoid carcinoma effectively treated with atezolizumab, carboplatin, paclitaxel, and bevacizumab. (2022) - Sawatari, Kosuke; Izumi, Motohiro; Sone, Risa; Hattori, Tsuyoshi; Sugimoto, Akira; Eguchi, Yosuke; Mamoto, Takashi
Abstract: Pulmonary sarcomatoid carcinoma (PSC) is an extremely rare neoplasm with poor prognosis and no established treatment. A 50-year-old man presented with fever, was found to have a mass measuring 14 cm in the right upper lobe of the chest, along with right pleural effusion on computed tomography (CT). Positron emission tomography-CT revealed abnormal tracer uptake in the area corresponding to the mass in the upper lobe. Hence, convex-probe endobronchial ultrasound-guided transbronchial needle aspiration was performed. Histological examination revealed dense proliferation of spindle tumor cells and no programmed death-ligand 1 (PD-L1) expression. Thus, he was diagnosed with PSC (cT4N0M1a, clinical stage IVA), and four-agent combination chemotherapy with atezolizumab, carboplatin, paclitaxel, and bevacizumab was initiated. Marked shrinkage of the mass and symptomatic improvements were observed following the treatment initiation. Tumor shrinkage was further noted after shifting to maintenance therapy with atezolizumab and bevacizumab; the patient exhibited no symptom exacerbation 2 years later and continued the treatment. Our case showed that four-agent combination chemotherapy with atezolizumab, carboplatin, paclitaxel, and bevacizumab could be an effective treatment option for advanced PSC with or without PD-L1 expression.